Validity of Ultrasound Lung Comets for Assessment of the Severity of Interstitial Pneumonia. (30th November 2017) - Asano, Mariko; Watanabe, Hiroyuki; Sato, Kazuhiro; Okuda, Yuji; Sakamoto, Sho; Hasegawa, Yukiyasu; Sudo, Kazuhisa; Takeda, Masahide; Sano, Masaaki; Kibira, Satoshi; Ito, Hiroshi
Abstract : Objectives: Ultrasound (US) lung comets are often observed in patients with interstitial lung disease or congestive heart failure, but few studies have explored the clinical importance of US lung comets in patients with the former condition. We explored whether the US lung comet number could be used to assess the severity of interstitial pneumonia. Methods: Forty stable patients with interstitial pneumonia were examined. Lung comets evident on transthoracic US imaging in 12 selected regions of the posterior chest wall were analyzed. We defined lung comets accompanied by thickened and irregular pleural lines as interstitial US lung comets; these predominated in patients with interstitial pneumonia. The total number of interstitial US lung comets was correlated with the data from chest high‐resolution computed tomography, pulmonary function tests, serologic tests, and the 6‐minute walk test. Results: The 40 patients included 16 with idiopathic pulmonary fibrosis and 24 with nonspecific interstitial pneumonia. Thirty‐four patients had interstitial US lung comets, which were more common in the lower than the upper lung area. Good correlations were evident between the lung comet number and the extent of the reticular pattern on chest high‐resolution computed tomography ( r = 0.710; P < .01), predicted forced vital capacity ( r = −0.614; P < .01), and lung diffusion capacity for carbon monoxide ( r = −0.577; P < .01). Notably, the lung comet number had a strong negative correlation with the percutaneous oxygen saturation level after the 6‐minute walk test ( r = −0.751; P < .01). Conclusions: The number of interstitial US lung comets evident on transthoracic US imaging may be a valuable marker of disease severity in patients with interstitial pneumonia.